Growth and Exploitation Rate of Mystus nigriceps - Rukayah, Siti; Lestari, Windiarini; Nuryanto, Agus; Mahmoud, Hanan Hassan Alsheikh (Biosaintifika: Journal of Biology & Biology Education, 2025)
Mystus nigriceps is among the bagrid fish species that live in freshwater ecosystems, including Cicingguling River, Kebumen Regency, Central Java, Indonesia. Despite the economic importance and exploitation for food, the fish is rarely studied. Meanwhile, studies on the growth pattern and exploitation rate of M. nigriceps in the Cicingguling River are important because the population is also affected by river fragmentation due to reservoir development. Therefore, this study aims to analyze the growth pattern and exploitation rate of M. nigriceps in the Cicingguling River. Sampling was carried out using the purposive random sampling method in the Cicingguling River. A total of 9 stations were divided into 3 zones for 1 year, with a frequency of 12 times and an interval of once a month. The results showed that a length-weight relationship had an average b-value of 3.11, indicating a positive allometric pattern (b>3). The condition factor of female M. nigriceps (2.404) was higher than that of male fish (2.06). Total mortality (Z) was estimated at 4.85 per year, consisting of natural mortality (M) at 3.59 per year and fishing mortality (F) at 1.26 per year. These values suggest that the mortality of M. nigriceps is primarily driven by natural causes rather than fishing pressure. The exploitation rate was 0.26 per year, which is relatively low as it remains below the optimum threshold (Eoptimum = 0.5). This information is essential for fisheries management as a basis for M. nigriceps conservation in the Cicingguling River